2017
DOI: 10.1007/s12560-017-9292-6
|View full text |Cite
|
Sign up to set email alerts
|

Risk Analysis and Occurrence of Hepatitis E Virus (HEV) in Domestic Swine in Northeast Brazil

Abstract: Anti-HEV antibodies were detected in animals from abattoir and in farms from northeast Brazil. Our results suggest that HEV is highly disseminated in the swine population and might present a great risk to animal handlers and for consumption of raw or undercooked meat and meat products in northeast Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 30 publications
1
11
0
3
Order By: Relevance
“…Our results are the first confirmation of HEV circulating among domestic swine farms in Northeast Brazil. The HEV RNA prevalence rate found here is markedly low considering the seroprevalence rates of up to 95% found in the same region 9 . Nevertheless, our findings are similar to those obtained in other countries such as Germany, China, Japan, and India 13 …”
supporting
confidence: 84%
See 1 more Smart Citation
“…Our results are the first confirmation of HEV circulating among domestic swine farms in Northeast Brazil. The HEV RNA prevalence rate found here is markedly low considering the seroprevalence rates of up to 95% found in the same region 9 . Nevertheless, our findings are similar to those obtained in other countries such as Germany, China, Japan, and India 13 …”
supporting
confidence: 84%
“…A total of 119 faecal samples were individually collected in 2017 from two to six-month-old animals from eight farms using both intensive and extensive production systems located within a high HEV seroprevalence area 9 . Viral RNA was extracted from a 200 µL faecal suspension using the ReliaPrep™ Viral Total Nucleic Acid Purification Kit (Promega, Brazil) and screened by a previously described real-time polymerase chain reaction (RT-PCR) method 10 using the NextGeneration ECO One-Step HotStart RT-qPCR Kit (DNA Express Biotecnologia, Brazil).…”
mentioning
confidence: 99%
“…In addition, HEV gt3 has been found in local pig populations and humans. HEV gt1 infection is very uncommon (Passos-Castilho et al 2015;de Oliveira-Filho et al 2017). The epidemiology of HEV in Latin America appears to bear close similarity to that found in developed countries such as Europe.…”
Section: Latin Americamentioning
confidence: 90%
“…Various farm production systems are associated with HEV prevalence [54][55][56]. The factor 'farming system' comprises management measures that probably have a direct effect on aspects of the MSEIR-En modelling for HEV transmission.…”
Section: Farm Demographicsmentioning
confidence: 99%
“…On the contrary, De Oliveira-Filho et al found no difference between intensive (indoor) farms and extensive (free-ranging) farms (2017). Semi-intensive production was associated with a lower HEV seroprevalence, although the definition of semi-intensive was not given [55].…”
Section: Farm Demographicsmentioning
confidence: 99%